Strategi Pemanfaatan Sampah Rumah Tangga menjadi Pupuk Organik pada Program Kampung Bantar di Kelurahan Pakuan Baru Kota Jambi - Parmadi; Hastuti, Dwi; Hardiani; Umiyati, Etik; Achmad, Erni; Maisyarah, Nyimas Dian (WIDA Publishing, 2023)
Kampung Bantar (Bersih, Aman, dan Pintar), known as the Kampung Bersih program, serves as a sustainable initiative to accelerate development of Jambi City. This program, aiming to instill a clean and healthy environmental awareness in every communities at the RT (Rukun Tetangga) level, is being implemented across all kelurahan and kecamatan within Jambi City. The success of implementing the smart city concept in Jambi City reflects a strong commitment from the local government to drive household innovation towards “smart city” status, complete with regulated and planned internet access and services. The implementation of organic waste management extends beyond household levels, reaching into the vicinity of tourist attractions. The primary objective is to ascertain the amount of waste generated as a result of tourism activities and understand the efforts made by the local residents to address this issue. Kelurahan Pakuan Baru, with its potential as a tourist village, serves as the site for one of the community empowerment programs aimed at enhancing the well-being of its residents. The community empowerment process is grounded in the local potential of the kelurahan, with a focus on sustainability and maintaining a balance in the cleanliness of the environment.